(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2021)
A pot experiment was conducted to evaluate the effects of four levels of lead (50, 100, 150 and 200 mg/kg) treatment on wheat (Triticum aestivum L.) and its amelioration by cowdung, poultry litter and lime. The lengths, fresh and dry weights of shoot and root decreased with increasing level of lead as well as the macronutrients compared to the control. The maximum reduction was observed in the pots treated with 200 mg/kg lead. The highest reduction in macronutrient content was also observed in 200 mg/kg Pb treated pot whereas N, P, K, Ca and Mg concentration was reduced by 0.41, 0.019, 1.15, 0.38 and 0.071% for shoot and 0.512, 0.071, 0.17, 0.51 and 0.122% for root, respectively. Lead concentration in roots and shoots increased with increasing level of lead treatment compared to the control. Cowdung was shown to be most effective, followed by poultry litter and lime. This particular organic manure had considerably greater decreasing impacts in lead uptake by wheat crops. Cowdung treated pots increased fresh and dry weight by 14.56 and 13.28% for grain, 7.58 and 7.08% for shoot and 2.41 and 2.06% for root compared to pot treated with 100 mg/kg lead. J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(2): 69-76